A Figurine with a Possible Early Aramaic Inscription. (2nd July 2020) - Richey, Madadh
Abstract : This article deals with an inscribed amulet in the form of an animal that was acquired by the British Museum in 1883 with the claim that its provenience was Tartus, opposite the ancient Phoenician city of Arwad. The five graphemes of the inscription, trztn, are interpreted as written in early Aramaic script, dated to the 9th or 8th centuries BCE. Most plausibly the graphemes constitute a flora-derived personal name, Tirzatan, likely that of the onetime owner of the amulet. Strengths and weaknesses of other interpretative options are also considered.